SOCIAL-PSYCHOLOGICAL FACTORS INFLUENCING THE PROCESS OF ADAPTATION OF CONSCRIPTS TO MILITARY SERVICE - Tajiev Umid Tohirovich (American Journals, 2022)
This article provides information on the concept of conscript military service in Uzbekistan, the process of accustoming conscripts to military service, and social and psychological factors affecting the adaptation process.
Keywords: citizens, military service, commitment, habituation, psychology, team, idea, conditions.